Upaya Meningkatkan Keterampilan Menulis Bahasa Inggris Melalui Teknik EGRU Pada Siswa Kelas X SMK Negeri 1 Ende - Separ, Fransiskus Maria (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to improve students' writing skills and improve mastery of sentence patterns and vocabulary in learning English and improve students' writing learning outcomes, especially in class X of SMK Negeri 1 Ende, Mautapaga Village, East Ende District, Ende Regency, East Nusa Tenggara. The subjects of this research were 39 students of class X- SMK Negeri 1 Ende. This research was carried out in three cycles, namely cycle I presented short message texts with the topic "Announcement", while cycles II and III presented descriptive texts with the topic "Description of people or things". In both cycles using the EGRU-based Literacy learning model, the results of data analysis showed that the average writing test score in cycle I was 65.38, the average writing test score in cycle II was 70.83 and in cycle III was 74.84. In cycle I there were 56.41% of students classified as active and very active, in cycle II there were 97.44% of students classified as active and very active, while in cycle III all students appeared active. Based on the student response questionnaire, out of 39 people, 36 people stated that they agreed to use EGRU in learning English, especially writing. Based on this classroom action research, EGRU has a big influence on students' writing activities, skills and learning outcomes. Therefore, it is hoped that similar teachers will use EGRU with a literacy approach in learning English, especially writing.